Edukasi Kesehatan Penyakit Stroke pada Usia Produktif melalui Diskusi Publik bersama Yastroki - Mogi, Amelia Haness; Novelia, Nina; Ganiem, Leila Mona (Penerbit Widina, Widina Media Utama, 2025)
Stroke is one of the leading causes of death and disability worldwide, including in Indonesia. This condition can affect anyone, including individuals in their productive years, due to risk factors such as hypertension, diabetes, obesity, and unhealthy lifestyles. The prevalence of stroke in Indonesia continues to rise, with an increasing number of cases occurring among people under the age of 50. Public discussion activity highlights the importance of Personal Social Responsibility (PSR) in raising public awareness about stroke, especially among people in their productive age. Collaboration between the fields of communication and medicine can produce more effective educational strategies by delivering information in a simpler and more understandable way. One of method is a public discussion titled